Performance of different mulching materials on soil moisture content, weed infestation and growth of maize (Zea mays L.) - Zin Mar Aung Aung; Thu Zar; Aung Zaw Htwe; Lwin Thuzar Nyein; Htay Htay Oo (Future Science, 2022)
Two field experiments were conducted at Yezin farm and Sepin research farm, Yamenthin, Myanmar to investigate the effect of different mulching materials on growth, soil moisture and weed infestation of maize and to identify the most Two field experiments were conducted at Yezin and Sepin research farms, Yamethin, Myanmar to investigate the effect of different mulching materials on growth, soil moisture and weed infestation of maize and to identify the most suitable mulching materials for maize cultivation in the study areas during the dry season (October, 2019 to March, 2020). The experiments used randomized complete block design (RCB) with three replications. No mulching and six mulching materials, including rice straw mulching, rice husk mulching, maize stover mulching, mung bean stover mulching, soybean stover mulching and white plastic polyethylene mulching were tested. NK-621 (120 days) was used as the tested variety. Different mulching materials showed higher plant height and SPAD value than no mulching whereas rice straw mulching was highest at both locations. The highest LAI was achieved from rice straw mulching at Yezin. At Yamethin, the maximum LAI (2.19) was recorded from rice straw mulching at maximum growth stage (MGS), LAI (2.71) observed from maize stover mulching at tasseling stage (TS). The maximum crop growth rate (CGR) (13.31 gm-2day-1) was achieved from rice straw mulching at Yezin and (14.19 gm-2day-1) at Yamethin. Soil moisture content and weed infestation were significantly different among different mulching materials at two locations. White plastic polyethylene mulching and rice straw mulching were observed as the most suitable for soil moisture content and minimal weed infestation. According to the results, rice straw mulching is the best in all parameters among the treatments for Yezin and Yamethin areas. suitable mulching materials for maize cultivation in the study areas during the dry season (October, 2019 to March, 2020). The experiments were assigned by using randomized complete block design (RCB) with three replications. A total of seven treatment; no mulching (T1) and six mulching materials including rice straw mulching (T2), rice husk mulching (T3), maize stover mulching (T4), mung bean stover mulching (T5), soybean stover mulching (T6) and white plastic polyethylene mulching (T7) were tested. The most widely sown variety, NK-621 (120 days) was used as the tested variety. Different mulching materials showed higher plant height and SPAD value than no mulching whereas rice straw mulching (T2) was highest at both locations. At three sampling times, the highest LAI was achieved from rice straw mulching (T2) at Yezin. At Yamenthin, the maximum LAI (2.19) was recorded from rice straw mulching at maximum growth stage (MGS), LAI (2.71) observed from maize stover mulching (T4) at tasseling stage (TS) and LAI (2.00) achieved from white plastic polyethylene mulching (T7) at grain filling stage (GFS). The maximum crop growth rate (CGR) (13.31 gm-2day-1) was achieved from rice straw mulching (T2) at Yezin and (14.19 gm-2day-1) at Yamenthin. Soil moisture content and weed infestation were significantly different among different mulching materials at two locations. White plastic polyethylene mulching and rice straw mulching were observed as the most suitable for soil moisture content and minimal weed infestation. According to the results, rice straw mulching is the best in all parameters among the treatments for Yezin and Yamenthin areas.